2019
DOI: 10.1111/jonm.12791
|View full text |Cite
|
Sign up to set email alerts
|

Iranian pre‐hospital emergency care nurses' strategies to manage workplace violence: A descriptive qualitative study

Abstract: Aim:To explore the experiences of Iranian nurses working in pre-hospital emergency care services and the strategies used to manage of workplace violence.Background: Pre-hospital emergency nurses are subject to workplace violence; however, little research addresses their experiences, particularly related to their strategies in dealing with workplace violence. Methods:A descriptive qualitative study that involved nineteen male nurses who were working in pre-hospital services collected data using semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
(41 reference statements)
2
36
0
Order By: Relevance
“…Nurses in this study stated that it was difficult for them to tolerate and cope with intentional violence, while they tend to tolerate unintentional violence from patients suffering from delirium or dementia. This finding, consistent with other studies (Dadashzadeh et al, 2019;Hogarth, Beattie, & Morphet, 2016), found that tolerance of WPV was related to the nurses' ability to understand unintentional violence related to the severity of the patient's conditions in comparison with intentional violence. Some participants in this study experienced horizontal violence from doctors, nurses and other staff: "I mean most of it [is] patient violence but you can get verbal violence from doctors all the time" (ICU1).…”
Section: Discussionsupporting
confidence: 92%
“…Nurses in this study stated that it was difficult for them to tolerate and cope with intentional violence, while they tend to tolerate unintentional violence from patients suffering from delirium or dementia. This finding, consistent with other studies (Dadashzadeh et al, 2019;Hogarth, Beattie, & Morphet, 2016), found that tolerance of WPV was related to the nurses' ability to understand unintentional violence related to the severity of the patient's conditions in comparison with intentional violence. Some participants in this study experienced horizontal violence from doctors, nurses and other staff: "I mean most of it [is] patient violence but you can get verbal violence from doctors all the time" (ICU1).…”
Section: Discussionsupporting
confidence: 92%
“…Strategies implemented by hospital staff in the face of violence and, more generally, of interpersonal difficulties are multiple. 35 They may involve communication strategies (with the use of rational explanation, seduction and empathy) and confrontational or flight-related behaviours. While the management of deviant behaviours can involve collective intervention, the strategies used to deal with difficult interactions are essentially individual.…”
Section: Discussionmentioning
confidence: 99%
“…44 The strategy of escape or flight has barely been dealt with in the existing literature so far. 35 There are sociological mechanisms at work behind these strategies. The caregiver-patient relationship in the ED has changed significantly and there is 'a growing intolerance among patients regarding the status of being hospitalised, and the dependence and even submission that this status implies'.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the second type of violence, the source of violence is the people working in medical departments or emergency wards who show violence against victims or their relatives [ 4 , 10 ]. It is worth noting that when violence is committed by employees, no disciplinary action is usually taken, because such a violence is attributed to staffs’ anger or troubles caused by issues in their workplace [ 4 , 11 ]. Nonetheless, being upset and angry cannot justify committing violence and aggression in the workplace, because it can have detrimental consequences for the organization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%